Marketing Communication Strategy Of Riyan Farm Hydroponic Vegetable (Case Of Riyan Farm Smes, Serang City) - Sri Mulyati; Nanang Krisdianto; Mohamad Arief Setiawan (Research Collaboration Community (RCC), 2021)
Riyan Farm is one of agricultural business that uses hydroponic method to grow vegetables in Serang City. However, many people of Serang City and the county around are still not knowing Riyan Farm’s hydroponic product which results in decreased sales. This requires Riyan Farm to determind the right marketing communication strategy. This study lasted for 7 months with several considerations. The research took place on RSS Pemda Housing Block D1 Banjarsari District Cipocok Jaya Serang City Banten. This research uses a benchmarking approach against other business that have similar products and have been successful in the market. Benchmarking method performed by collecting information from other Farm’s product through in-depth interviews and observation and other data that have reliable information as books and literature. The analysis tools used are Gap analysis, IFE matrix, EFE matrix and SWOT matrix. The Gap analysis based on marketing communication mix results in 7 recommendation of communication strategy. In order to create the applicative strategy that suits company’s environment, those 7 recommendations should be combined with the result of SWOT Analysis. The last of result shows 5 market communication alternative strategy.